2018
DOI: 10.21608/mjcu.2018.62818
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in Vitro Susceptibility Pattern of Fungal Pathogens in Immunocomprimised Patients with Pulmonary Fungal Infections

Abstract: Background: The frequency of fungal infections of the lung has increased particularly in immunocompromised patients. Early diagnosis and treatment is important to start antifungal therapy and to avoid unnecessary use of toxic antifungal agents. This study aimed to identify the common fungal species causing pulmonary infection in immunocompromised patients and their in vitro antifungal sensitivity pattern in Assiut University Hospitals (AUH). Subjects and Methods:This was a hospital based descriptive study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…where it was found that Amphotericin B is resistant and Itraconazole is sensitive. These results disagree with those of Ahmed [27]. reported that the most effective drugs for their isolates were Nystatin and amphotericin-B, the resistance was most commonly seen against Itraconazole followed by fluconazole and with Sheneef [28].…”
Section: Table5: Pediatric Oral Infection According To Type Lactationcontrasting
confidence: 98%
“…where it was found that Amphotericin B is resistant and Itraconazole is sensitive. These results disagree with those of Ahmed [27]. reported that the most effective drugs for their isolates were Nystatin and amphotericin-B, the resistance was most commonly seen against Itraconazole followed by fluconazole and with Sheneef [28].…”
Section: Table5: Pediatric Oral Infection According To Type Lactationcontrasting
confidence: 98%